Design and implementation of a web application for automated deployment of selected data engineering tools - Tsakunov, Ilya; Novotný, Ota, 1971-; Vencovský, Filip; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This diploma thesis addresses the challenge faced by smaller data engineering teams, where significant time is often dedicated towards infrastructure setup rather than pipeline development. The proposed solution is a web application that aims to simplify the deployment of selected data engineering tools on Kubernetes infrastructure running on cost-effective cloud providers such as Hetzner. The application's backend is developed using Python with the FastAPI framework, while its frontend is built with TypeScript and React. The application is evaluated through two distinct approaches. First, a practical demonstration project was prepared that involves a web scraping pipeline to extract real estate data from the two largest Czech portals for later visualization. Second, qualitative feedback on the application's usability and utility was gathered from the potential users.
Vedoucí práce: Ota Novotný
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data a analytika pro business [obor dipl. práce]; diplomové práce; master's theses